Levels and clinical significance of serum Hcy，PTH and β2⁃MG in maintenance hemodialysis patients with chronic renal failure - LI Min，ZHANG Yuqin，ZHANG Hongxu (Zhongguo linchuang yanjiu)
Objective To analyze the prognostic value of changes in serum levels of homocysteine（Hcy），parathyroid hormone（PTH），and β2-microglobulin(β2-MG）inpatients with chronic renal failure（CRF）undergoing maintenance hemodialysis. Methods A retrospective analysis was conducted on the clinical data of 180 CRF patients undergoing maintenance hemodialysis at Anhui No.2 Provincial People's Hospital from March 2022 to March 2024. Based on prognosis，the patients were divided into a good prognosis group（n= 138）and a poor prognosis group（n=42）. Clinical data and laboratory indicators，including plasma total cholesterol（TC），triglycerides（TG），hemoglobin（Hb），serum high-sensitivity C-reactive protein（hs-CRP），white blood cell count（WBC），neutrophil count（NEUT），Hcy，PTH， and β2-MG，were compared between the two groups. Binary logistic regression was used to analyze the factors influencing prognosis in CRF patients undergoing maintenance hemodialysis. Receiver operating characteristic（ROC） curves were plotted to evaluate the predictive value of laboratory indicators for patient prognosis.Results The good prognosis group was younger and had a shorter dialysis duration than the poor prognosis group，with lower serum levels of hs-CRP，Hcy，PTH，and β2-MG（P<0.05）. Binary logistic regression analysis showed that age ≥65 years，dialysis duration ≥10 months，and high levels of hs-CRP，Hcy，PTH，and β2-MG were risk factors for poor prognosis in CRF patients undergoing maintenance hemodialysis（P<0.05）. ROC analysis revealed that the AUC for serum Hcy，PTH，β2-MG ，and their combination in predicting prognosis were 0.884，0.885，0.867，and 0.893，respectively ，with sensitivities of 0.810，0.833，0.714，and 0.690，and specificities of 0.812，0.855，0.928，and 0.978，indicating high predictive efficacy. Conclusion The prognosis of CRF patients undergoing maintenance hemodialysis is influenced by age，dialysis duration，and serum levels of hs-CRP，Hcy，PTH，and β2-MG. Clinical monitoring of serum Hcy，PTH， and β2-MG levels can help predict patient prognosis.